Synthesis of carbides compounds from elemental powder by mechanical milling / Aznifa Mahyam Zaharudin, Rizal Mohamaed Noor and Rasdi Deraman - Zaharudin, Aznifa Mahyam; Mohamaed Noor, Rizal; Deraman, Rasdi (2005)
Silicon carbides (SiC), was prepared by mechanical milling using high planetary ball mill. Four parameters studied are the effect of milling time, effect of annealing temperature, effect of environment and effect of two stages of milling. Powders of silicon and graphite mixture were milled for 15 hours, 25 hours and 60 hours with ball to powder weight ratio (BPR) of 30:1 at 130 rpm. The as-milled samples were then annealed at 800°C, 1000°C and 1200°C. The phase formation and structural and morphology changes during mechanical milling were studied by X-ray diffraction (XRD), differential thermal analysis (DTA) and scanning electron microscopy (SEM). No formations of silicon carbide were found in powder milled for up to 60 hours. It was found that silicon carbide could be formed in powders milled for 15 hours, 25 hours or 60 hours after annealing in argon atmosphere at 1200°C. XRD peaks of silicon carbide in the annealed powder shows very low intensities and broad, indicating silicon carbide phase was in nano-phase. Using Scherrer equation, the average crystallite size calculated was 22 nm. In an effort to synthesized silicon carbide at lower milling time, two stages milling was performed. Results indicate that two stage milling improved production of silicon carbide as more silicon carbide formed. Extended second milling produced silicon carbide crystallite size of 9 nm.